USE OF ELECTRONIC CIGARETTES BY BIOLOGY STUDENTS AT A PRIVATE UNIVERSITY IN ANÁPOLIS, GOIÁS (CIPEEX, 2025)
Electronic cigarettes (EC) were introduced to the market with the main objective of being a replacement option for conventional cigarettes, promoting the idea that they are less harmful to health and less addictive. However, these devices are associated with Electronic Vaping-Associated Lung Injury (EVALI), which is highly harmful to health, in addition to their widespread use and ease of access today. This study aimed to evaluate the use of electronic cigarettes by university students in the biological sciences at a private university in Anápolis, Goiás. This is a quantitative descriptive study, with the application of an online questionnaire to university students in the biological sciences who agreed to participate in the study and signed a free and informed consent form (FICF). The sample obtained revealed that 10% of respondents were EC users, in addition to 16.25% who were users of other types of cigarettes. Among EC users, the majority identified themselves as female, aged between 18 and 24 years old, with a very low degree of dependence, and the use of the devices was closely associated with socializing and moments of relaxation. Despite the low rates of EC users identified, due to the severity of lung damage caused by ECs, it is still important to develop strategies to raise awareness about the possible negative effects of electronic cigarettes, in addition to debunking possible false ideals about their use.
Keywords: Electronic Nicotine Delivery System; Smoking; Odorants